2007
DOI: 10.1104/pp.107.098335
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Regulation of Fruit Set and Growth in Tomato

Abstract: The role of gibberellins (GAs) in tomato (Solanum lycopersicum) fruit development was investigated. Two different inhibitors of GA biosynthesis (LAB 198999 and paclobutrazol) decreased fruit growth and fruit set, an effect reversed by GA 3 application. LAB 198999 reduced GA 1 and GA 8 content, but increased that of their precursors GA 53 , GA 44 , GA 19 , and GA 20 in pollinated fruits. This supports the hypothesis that GA 1 is the active GA for tomato fruit growth. Unpollinated ovaries developed parthenocarp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
208
1
43

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(269 citation statements)
references
References 56 publications
17
208
1
43
Order By: Relevance
“…S6F) are consistent with previous reports of increased bioactive GA content and GA20ox transcription after pollination (Serrani et al, 2007(Serrani et al, , 2008de Jong et al, 2011). However, it was not previously known that a GA20ox transcript increases particularly in the funiculus, which is also a site of high auxin activity (Pattison and Catalá, 2012;Fig.…”
Section: A Map Of Hormone-related Gene Expression During Early Fruitsupporting
confidence: 82%
“…S6F) are consistent with previous reports of increased bioactive GA content and GA20ox transcription after pollination (Serrani et al, 2007(Serrani et al, , 2008de Jong et al, 2011). However, it was not previously known that a GA20ox transcript increases particularly in the funiculus, which is also a site of high auxin activity (Pattison and Catalá, 2012;Fig.…”
Section: A Map Of Hormone-related Gene Expression During Early Fruitsupporting
confidence: 82%
“…Our findings point to GA/DELLA-mediated control of mitotic exit in Arabidopsis leaves as well, at least under stress conditions. Furthermore, our finding that PAC and DELLA stabilization induce endoreduplication is in contrast to earlier observations based on GA addition experiments and mutant analysis showing that GA promotes endoreduplication in, for instance, pea (Pisum sativum; Mohamed and Bopp, 1980), Arabidopsis hypocotyls (Gendreau et al, 1999;Saibo et al, 2003), and tomato (Solanum lycopersicum) fruits (Serrani et al, 2007). This, again, suggests that the effects of hormones depend greatly on concentration, tissue or cell type, species, and environmental parameters.…”
Section: Dellas Control Cell Proliferation By Inducing Differentiationcontrasting
confidence: 56%
“…For instance, it was shown that expression of a GA 20-oxidase gene was induced by pollination in tomato (Rebers et al 1999;Serrani et al 2007), and the importance of SlDELLA, which represses GA signaling and tomato fruit set, has also been demonstrated (Marti et al 2007). In additional, IAA9 and ARF8, both transcriptional regulators of the auxin response, were shown to be part of an important signal for fruit set (Wang et al 2005;Goetz et al 2007).…”
mentioning
confidence: 99%